Iron Deficiency in Inflammatory Bowel Disease Is Associated With Low Levels of Vitamin D Modulating Serum Hepcidin and Intestinal Ceruloplasmin Expression. Issue 1 (13th January 2022) - Stallhofer, Johannes; Veith, Lisa; Diegelmann, Julia; Probst, Philipp; Brand, Stephan; Schnitzler, Fabian; Olszak, Torsten; Török, Helga; Mayerle, Julia; Stallmach, Andreas; Beigel, Florian
Abstract : INTRODUCTION: Iron deficiency and vitamin D deficiency are common comorbidities in inflammatory bowel disease (IBD). Accumulating evidence indicates that active 1, 25-dihydroxyvitamin D (1, 25(OH)D) may enhance iron absorption by suppressing hepcidin. We investigated the influence of vitamin D on iron metabolism in patients with IBD and on the expression of genes facilitating intestinal epithelial iron absorption. METHODS: Iron parameters and serum levels of 25-hydroxyvitamin D (25(OH)D), 1, 25(OH)D, and hepcidin were measured in 104 adult patients with IBD (67 with Crohn's disease and 37 with ulcerative colitis). Genes involved in iron absorption were tested for induction by 1, 25(OH)D in Caco-2 cells, which resemble the small intestinal epithelium. RESULTS: In multiple regression models controlling for age, sex, body mass index, smoking status, disease activity, and C-reactive protein levels, low 25(OH)D levels were associated with iron deficiency in patients with IBD (β [SE] = −0.064 [0.030], P = 0.029). Vitamin D sufficiency was associated with increased levels of ferritin (β [SE] = 0.25 [0.11], P = 0.024) and transferrin saturation (β [SE] = 8.41 [4.07], P = 0.044). Higher 1, 25(OH)D:25(OH)D ratios were associated with lower hepcidin levels (β [SE] = −4.31 [1.67], P = 0.012). Especially in Crohn's disease, increased 1, 25(OH)D correlated with higher transferrin saturation (β [SE] = 0.43 [0.18], P = 0.027). Furthermore, 1, 25(OH)D strongly induced the expression of the ferroxidase ceruloplasmin in Caco-2 cells. DISCUSSION: Low vitamin D levels in IBD correlate with iron deficiency. Vitamin D may ameliorate iron deficiency, potentially by downregulating hepcidin and upregulating ceruloplasmin, enhancing intestinal iron absorption.